Graduate unemployment and underemployment in Sri lanka - An analysis - Kularatne, W.G. (My University, 1982)
Unemployment and Underemployment among U n i v e r s i t y g r a d u a t e s has been a c o n s p i c u o us p r o b l e m i n S r i L a n k a s i n c e m i d - s i x t e e s . This i s a c r u c i a l p r o b l e m t h a t b e a r s p o l i t i c a l , s o c i a l and economic c o n s e q u e n c e s s p e c i a l l y i n a d e v e l o p i n g c o u n t r y and d e s e r v e s c o n t i n u o u s assessment. I n such a c o n t e x t , a c o m p r e h e n s i v e study i n terms of q u a l i t a t i v e and q u a n t i t a t i v e a s p e c ts i s c a l l e d f o r. I n t h i s s t u d y , a t t h e o u t s e t , an a t t e m p t i s made t o b u i l d a c o n c e p t u a l framework by a n a l y s i n g t h e c o n c e p t of human c a p i t a l , growth of e d u c a t ed unemployment p a r t i c u l a r l y i n d e v e l o p i n g c o u n t r i es i n s p i t e of i n v e s t m e n t i n human c a p i t a l and t h e s i t u a t i o n i n S r i L a n k a . The n e x t s t a g e of t h e s t u d y i s t h e d e f i n i t i o n of t h e c o n c e p t s of unemployment and u n d e r e m p l o y m e n t i n t h e S r i Lankan c o n t e x t and i d e n t i f i c a t i o n of t h e n a t u r e and t h e e x t e n t o f t h e p r o b l e m i n t h e c o u n t r y . In t h is i n s t a n c e the l a c k of an a c c e p t e d d e f i n i t i o n and t h e a m b i g u i t y of terms used and t h e p a u c i t y of d a t a g e n e r a t e d by s y s t e m a t i c s u r v e y s i n h i b i t s t he d e v e l o p m e n t o f a c l e a r view of t h e p r o b l e m i n t h e c o u n t r y . Next an a n a l y s i s i s made on t h e n a t u re o f the o u t p u t of S r i L a n k a n U n i v e r s i t i e s and how t h e l a b o u r m a r k e t , b o t h p r i v a t e and p u b l ic s e c t o r s , has changed u n f a v o u r a b l y f o r t he U n i v e r s i t y g r a d u a t e s ; how t h e g o v e r n m e n t s have t r i e d to i n t e r v e n e t o r e c t i f y t h i s s i t u a t i o n and why these s t e p s c o u l d n o t a r r i v e at a l o n g term s o l u t i o n to t h e p r o b l e m . A g a i n s t t h i s backdrop o f the s i t u a t i o n i n S r i L a n k a , an a t t e m p t i s made t o e v a l u a t e t h e e d u c a t e d unemployment p r o b l e m i n t h e n e i g h b o u r i n g s u b c o n t i n e n t i n o r d e r to b r o a d en t h e u n d e r s t a n d i n g of t h e c o m p l e x i t i e s o f t h e p r o b l em I n s p i t e o f t h e d i f f e r e n c e s i n t h e m a g n i t u de o f the p r o b l e m , many f a c e t s of-lb€ I n d i an e d u c a t e d unemployment p r o b l e m r e s e m b l e t he S r i Lankan s i t u a t i o n . Next a case s t u d y i s u n d e r t a k e n i n o r d e r to u n d e r s t a n d t he q u a l i t a t i v e a s p e c t o f t h e p r o b l e m and t h e f i n d i n g s o f t h e c a s e s t u d y m a i n l y e l u c i d a te t h a t t h e r e e x i s t s d i s c r i m i n a t i o n a g a i n st women, r u r a l y o u t h and t h e p o o r s e c t i o n of t h e s o c i e t y w i t h r e g a r d to employment i n t h e coun t r y . F i n a l l y an a t t e m p t i s made t o e v a l u a te t h e v a r i o u s f a c t o r s t h a t c o n t r i b u t e d to t h is p r o b l e m p l a c i n g them w i t h i n the b r o a d er s o c i o economic c o n t e x t i n t h e c o u n t r y . The o b j e c t i v e of t h i s a n a l y s i s i s t o i d e n t i f y t h e major and p e r i p h e r a l v a r i a b l e s a s s o c i a t ed w i t h the p r o b l e m and t o a s s e s s the r e m e d i al m e a s u r e s t o a m e l i o r a t e them i n t h e S r i L a n k an c o n t e x t .